Pengaruh Gender, Tekanan Ketaatan, Tekanan Anggaran Waktu Kompleksitas Tugas dan Pengalaman Auditor Terhadap Audit Judgment - Bimawan, Fitnantyo (Graha Akuntansi, 2022)
Framework of this research plan is based on considerations of motivation attitude of professionalism among auditors with the leadership of the CAC. In an audit process conducted by the firm will set up a team consisting of men and women, in decision-making process usually occurs a few conflicts between men and women. This is similar to research conducted by Rahmawati and Setyaningtyas in 2004. In addition, this study is a replication of research conducted by Hartanto and Kusuma (2000), which examines the effect of obedience pressure on audit judgments. Of the few existing references such as research conducted Jamilah et al, Rahmawati, Zulaikah and other most talked about gender, compliance and audit judgments pressure. Thus, the hypothesis was first proposed) gender did not influence audit judgments 2) pressures affect compliance audit judgments 3) the complexity of the task affect audit judgments. Unit analysis of this study is the auditors who work pad KAP in Semarang, senior and junior level auditor who was taken by a random sampling. After doing the questionnaire, the sample chosen for analysis as much as 41 people. Given this continued research is expected to issue about auditors will audit judgments obtained in a more comprehensive solution.